Development and characterization of lipid-based nanosystems: effect of interfacial composition on nanoemulsion behavior - Silva, Hélder D. (2020)
Nanoemulsions were successfully developed through high-pressure homogenization. The layer-by-layer electrostatic technique was used for the subsequent deposition of a chitosan and alginate polyelectrolyte layers, thus leading to the development of a multilayer nanoemulsion. The effect of polyelectrolytes concentration in the development of multilayer nanoemulsions was evaluated in terms of hydrodynamic diameter (Hd), polydispersity index (PdI), zeta potential (Zp), and curcumin encapsulation efficiency. The interactions between polyelectrolytes and nanoemulsion were further analyzed using Fourier transform infrared (FTIR) spectroscopy and quartz crystal microbalance (QCM), while curcumin degradation was determined through the evaluation of the antioxidant capacity of the nanosystems. Results showed an encapsulation efficiency of 99.8 ± 0.8% and a loading capacity of 0.53 ± 0.03% (w/w). The presence of the multilayers leads to an increase of the Hd of the nanosystems, from 80.0 ± 0.9 nm (nanoemulsion) to 130.1 ± 1.5 nm (multilayer nanoemulsion). Release profiles were evaluated at different conditions, fitting a linear superposition model to experimental data suggests an anomalous behavior, being the relaxation of the surfactant and polyelectrolytes the rate-determining phenomena in curcumin release. The developed nanosystems showed great potential for the incorporation of lipophilic bioactive compounds, in view of their application in food and pharmaceutical products.